Epilepsy-Associated UBE3A Deficiency Downregulates Retinoic Acid Signalling Pathway - Fang, Meimiao; Li, Yali; Ren, Jin; Hu, Ronggui; Gao, Xiaobo; Chen, Liang (Frontiers in Genetics, 2021)
Ubiquitin-protein ligase E3A (UBE3A) has dual functions as a E3 ubiquitin-protein ligase and coactivator of nuclear hormone receptors. Mutations or deletions of the maternally inherited UBE3A gene cause Angelman syndrome. Here, we performed transcriptome profiling in the hippocampus of Ube3am+/p+ and Ube3am-/p+ mice, and determined that the expression of the retinoic acid (RA) signalling pathway was downregulated in Ube3a-deficient mice compared to WT mice. Furthermore, we demonstrated that UBE3A directly interacts with RARα and may function as a coactivator of the nuclear receptor RARα to participate in the regulation of gene expression. Loss of UBE3A expression caused the downregulation of the expression of RA-related genes, including Erbb4, Dpysl3, Calb1, Pten and Arhgap5 in Ube3am-/p+ mice brain tissues. This work revealed a new role for UBE3A in regulating retinoic acid (RA) signalling downstream genes and hopefully to shed light on the potential drug target of AS.